Analisis Minat Pengunjung Terhadap Aktivitas Berkuda Di Bromo - Steve Elia Amadeus; Davin Fernando; Jessica Natania Vinata; Budi Setiawan (Indonesian Journal Publisher, 2025)
The Bromo area, as one of the popular tourist destinations in Indonesia, offers a variety of interesting activities, including horse riding, which not only provides a unique experience for tourists, but also contributes significantly to the local economy. This research aims to explore the factors that influence visitors' interest in horse riding activities in the Bromo area and their implications for the management of tourist destinations. Horse riding activities in Bromo attract the attention of domestic and foreign tourists, increasing their satisfaction through deep emotional experiences amidst stunning natural views. Factors that influence visitor interest include comfort, safety, and the quality of the facilities provided. This research also shows that equestrian activities not only impact the local economy, but also contribute to cultural and environmental preservation. On the other hand, there are challenges such as high horse riding fees, which can limit accessibility for some tourists. Trekking activities are an alternative for tourists who want to experience direct contact with nature. These two activities complement each other in increasing the attractiveness of the Bromo area as a tourist destination. These findings provide insight for tourism managers to develop sustainable tourism, improve the welfare of local communities, and strengthen tourist attractions by paying attention to safety, security, comfort and accessibility factors for visitors.